2020
DOI: 10.1186/s12913-020-4977-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding in the Australian aged care sector of reablement interventions for people living with dementia: a qualitative content analysis

Abstract: Background: Reablement has potential for enhancing function and independence in people with dementia. In order to enhance the use of evidence-based reablement in this population, this study sought to understand the current practices and needs of the sector around these interventions. Methods: A purposive sample of 22 Australian aged and community-care providers participated in a semistructured interview. Qualitative content analysis was applied to the data, with key themes interpreted within the context of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(37 citation statements)
references
References 42 publications
(59 reference statements)
0
37
0
Order By: Relevance
“…Eleven of these studies focused [ 16 26 ] on the perspective of physicians (predominantly primary care physicians) and two studies [ 27 , 28 ] on the perspective of nurses (registered nurses, licensed practical nurses and assistant nurses). One study interviewed providers of care for the elderly [ 29 ] and another one examined the perspective of primary care dementia coordinators [ 30 ]. The remaining fourteen studies [ 6 , 31 43 ] included various professions without differentiating between them.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven of these studies focused [ 16 26 ] on the perspective of physicians (predominantly primary care physicians) and two studies [ 27 , 28 ] on the perspective of nurses (registered nurses, licensed practical nurses and assistant nurses). One study interviewed providers of care for the elderly [ 29 ] and another one examined the perspective of primary care dementia coordinators [ 30 ]. The remaining fourteen studies [ 6 , 31 43 ] included various professions without differentiating between them.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [ 16 , 21 , 23 , 26 , 29 , 32 , 33 ] described regional influences on the use of care services, depending on where the people with dementia lived. The availability of services is mentioned as an important difference between rural and urban areas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing better support in re-enabling people with dementia is also vital and forms part of the post-diagnostic care (which also includes medication management [18]. In the Australian aged care sector, O'Connor and colleagues [19] showed that reablement interventions for people with dementia are varied, and to improve access to and usage of interventions, these should be multifaceted with a freely available resource outlining the different intervention components. This is supported to a degree by a recent meta-analysis by Backhouse et al [20], showing mixed evidence on the benefits of coordinated community interventions.…”
mentioning
confidence: 99%